A Multimodal Machine Learning Model in Pneumonia Patients Hospital Length of Stay Prediction - Anna Annunziata; Salvatore Cappabianca; Salvatore Capuozzo; Nicola Coppola; Camilla Di Somma; Ludovico Docimo; Giuseppe Fiorentino; Michela Gravina; Lidia Marassi; Stefano Marrone; Domenico Parmeggiani; Giorgio Emanuele Polistina; et al. (Big Data and Cognitive Computing)
Hospital overcrowding, driven by both structural management challenges and widespread medical emergencies, has prompted extensive research into machine learning (ML) solutions for predicting patient length of stay (LOS) to optimize bed allocation. While many existing models simplify the LOS prediction problem to a classification task, predicting broad ranges of hospital days, an exact day-based regression model is often crucial for precise planning. Additionally, available data are typically limited and heterogeneous, often collected from a small patient cohort. To address these challenges, we present a novel multimodal ML framework that combines imaging and clinical data to enhance LOS prediction accuracy. Specifically, our approach uses the following: (i) feature extraction from chest CT scans via a convolutional neural network (CNN), (ii) their integration with clinically relevant tabular data from patient exams, refined through a feature selection system to retain only significant predictors. As a case study, we applied this framework to pneumonia patient data collected during the COVID-19 pandemic at two hospitals in Naples, Italy—one specializing in infectious diseases and the other general-purpose. Under our experimental setup, the proposed system achieved an average prediction error of only three days, demonstrating its potential to improve patient flow management in critical care environments.